Analysis of The Implementation of Business Licensing for Partners of The National Nutrition Agency in Karanganyar Regency - Nabila Salma; Arief Budiono (Proceeding International Conference Restructuring and Transforming Law, 2026)
The implementation of the Free Nutritious Meal Program through a partnership with the National Nutrition Agency requires certainty of business legality, so that business licensing is a crucial aspect in ensuring the accountability and quality of nutrition services in the region. This study aims to explain the practice of implementing business licensing by the National Nutrition Agency partners at SPPG Karanganyar and its supporting and inhibiting factors. This study uses an empirical juridical method with a legislative and sociological approach, qualitative descriptive, with primary data through interviews and secondary data from laws and regulations and legal literature. The results show that the implementation of licensing has been carried out through the OSS system with the fulfillment of basic legalities such as NIB, business risk classification, and administrative and technical verification, although it still requires assistance in understanding business procedures and standards. Supporting factors include policy support, local government facilitation, and institutional coordination, while inhibiting factors include administrative obstacles, low licensing literacy, and social rejection due to the impact of business operations. In conclusion, the implementation of business licensing for partners of the National Nutrition Agency in Karanganyar Regency has been running, but its effectiveness still needs to be optimized through strengthening guidance, supervision, and harmonization of technical regulations.